Adult learners’ critical thinking in blended learning environment: a community of inquiry perspective - Jafarian, Sedigheh; Ismail, Maimunah; Asmuni, Azizan; Omar, Zoharah (2011)
This article presents preliminary results of a study on blended learning environment from a community of inquiry (COI) perspective as a tool for facilitating students’ critical thinking. The study was carried out among undergraduate students of Centre for External Education of Universiti Putra Malaysia. Data were derived from questionnaires that were administrated among students at the end of first semester 2010-2011 academic year. The results of this study showed that COI model is useful in facilitating critical thinking among distance education students. Specifically, there are relationships between social and teaching presence and critical thinking in the blended learning environment. There was no significant difference in mean for male and female students for the critical thinking. Implications to HRD are discussed.